2021
DOI: 10.1111/jvh.13458
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis E‐Associated Hospitalizations in the United States: 2010–2015 and 2015–2017

Abstract: Hepatitis E is considered rare in the United States (US) despite its widespread occurrence in Asian and African countries. The objective of this study was to describe the characteristics of hepatitis E‐related pregnancies and acute‐on‐chronic liver failure and analyse trends for hepatitis E diagnosis among hospitalized patients in the US. We examined data from the 2010–2017 National Inpatient Sample from Healthcare Cost and Utilization Project to determine mortality, morbidity, pregnancy diagnoses, chronic liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 44 publications
4
11
0
Order By: Relevance
“…National Inpatient Sample (NIS) data from Healthcare Cost and Utilization Project showed the rate of hospitalization due to hepatitis E increased from 3.7 per 10 million in 2010 to 6.4 per 10 million in 2015. Although hospitalization is still low in the United States, the increasing rate is worrisome[ 20 ]. The National Health and Nutrition Examination Survey (NHANES) data also demonstrated an increase in HEV seropositivity (IgG/IgM) from 5% in 2013-2014 to 7.7% in 2015-2016.…”
Section: Epidemiologymentioning
confidence: 99%
“…National Inpatient Sample (NIS) data from Healthcare Cost and Utilization Project showed the rate of hospitalization due to hepatitis E increased from 3.7 per 10 million in 2010 to 6.4 per 10 million in 2015. Although hospitalization is still low in the United States, the increasing rate is worrisome[ 20 ]. The National Health and Nutrition Examination Survey (NHANES) data also demonstrated an increase in HEV seropositivity (IgG/IgM) from 5% in 2013-2014 to 7.7% in 2015-2016.…”
Section: Epidemiologymentioning
confidence: 99%
“…Some studies have explored the impact of sporadic HEV infection on the health of pregnant women and their fetuses or neonates in developed countries and contemporary China, where HEV-3 and HEV-4 infections play a dominating role and lead to sporadic cases [ 4 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. However, these studies have provided conflicting conclusions [ 4 , 17 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have explored the impact of sporadic HEV infection on the health of pregnant women and their fetuses or neonates in developed countries and contemporary China, where HEV-3 and HEV-4 infections play a dominating role and lead to sporadic cases [ 4 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. However, these studies have provided conflicting conclusions [ 4 , 17 , 18 , 19 , 20 , 21 , 22 ]. For instance, Bouthry et al [ 20 ] reported that HEV-infected pregnant women in France exhibited nonspecific symptoms or asymptomatic alanine aminotransferase elevation, and no adverse outcomes were noted in these women or their neonates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In countries prevalent with HEV1 and HEV2, hepatitis E‐induced high mortality in pregnant women still exists and remains a serious and severe public health problem 3 . In developed countries and China where HEV3 and HEV4 are prevalent, high mortality in HEV‐infected pregnant women is rarely seen 4–6 but relative high rate of premature delivery was reported 7,8 . There is currently no approved drug against HEV.…”
Section: Introductionmentioning
confidence: 99%